Effects of extremely low frequency electromagnetic field on the health of workers in automotive industry. (December 2013) - Liu, Xin; Zhao, Longyu; Yu, Duo; Ma, Shumei; Liu, Xiaodong
<x xml:space="preserve">Abstract</x> Objective. To observe the effects of extremely low frequency electromagnetic fields (ELF-EMFs) in automotive industry on occupational workers. Methods. A total of 704 workers were investigated, and 374 workers were chosen and divided into two groups (control group and exposure group) according to the inclusive criteria, namely male with age 20–40 years old and ≥ 2 years of exposure. The intensities of ELF-EMFs and noise were detected with EFA-300 Field Analyzer (Narda company, Pfullingen, Germany) and AWA5610D integrating sound level meter (Hangzhou Aihua Instruments Co., Ltd, Hangzhou, China), respectively. Survey data were collected by questionnaire, and the physical check-up was done in hospital. All the data were input into SPSS17.0 software (SPSS Inc, Chicago, USA), and the appropriate statistic analyses were carried out. Results. The intensity of EMFs in exposure group was significantly higher than that in control group (p < 0.05), while the noise in two workplaces showed no difference (p>0.05). The survey data collected by questionnaires showed that the symptoms of loss of hair in exposure group were significantly different as compared with that in control group (p < 0.05). The check-up parameters of cardiovascular, liver and hematology system showed significant differences between the two groups (p < 0.05). Conclusions. Survey and check-up data suggest that exposure to ELF-EMFs might have effects on the nervous, cardiovascular, liver, and hematology system of workers.